2018
DOI: 10.1080/15374416.2018.1469093
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Associations among Relational Victimization, Targeted Rejection, and Suicidality in Adolescents: A Prospective Study

Abstract: This study examined associations between multiple types of interpersonal and noninterpersonal stressors and the subsequent occurrence of suicide ideation and attempts among female adolescents. Adolescents ages 12 to 18 years old (n = 160) at elevated risk for suicidal thoughts and behaviors were followed for 18 months, divided into two 9-month epochs for data analysis (Periods 1 and 2). Exposure to acute relational victimization, targeted rejection, nonspecified interpersonal, and noninterpersonal life stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…In a second longitudinal study, exposure to interpersonal life events interacted with a multilocus genetic profile score to prospectively predict increases in depressive symptoms in adolescents but, again, these effects were specific to interpersonal stressors (Feurer et al, 2017; see also Starr et al, 2017;Starr, Dienes, Li, & Shaw, 2019). Finally, a third study found that interpersonal life events involving targeted rejection precipitated onset of depression three times faster than other types of major life events (Slavich, Thornton, Torres, Monroe, & Gotlib, 2009; see also Massing-Schaffer et al, 2019). Moreover, when the impact of these stressors has been examined in youth assessed longitudinally, only interpersonal life events involving targeted rejection have been found to predict within-person changes in intracellular signaling molecules that are implicated in depression pathogenesis (Murphy, Slavich, Chen, & Miller, 2015;Murphy, Slavich, Rohleder, & Miller, 2013).…”
Section: Interpersonal Life Stress and Depressionmentioning
confidence: 92%
“…In a second longitudinal study, exposure to interpersonal life events interacted with a multilocus genetic profile score to prospectively predict increases in depressive symptoms in adolescents but, again, these effects were specific to interpersonal stressors (Feurer et al, 2017; see also Starr et al, 2017;Starr, Dienes, Li, & Shaw, 2019). Finally, a third study found that interpersonal life events involving targeted rejection precipitated onset of depression three times faster than other types of major life events (Slavich, Thornton, Torres, Monroe, & Gotlib, 2009; see also Massing-Schaffer et al, 2019). Moreover, when the impact of these stressors has been examined in youth assessed longitudinally, only interpersonal life events involving targeted rejection have been found to predict within-person changes in intracellular signaling molecules that are implicated in depression pathogenesis (Murphy, Slavich, Chen, & Miller, 2015;Murphy, Slavich, Rohleder, & Miller, 2013).…”
Section: Interpersonal Life Stress and Depressionmentioning
confidence: 92%
“…At the peer group level, adolescence is marked by the introduction of a new form of peer status, reflecting adolescents' dominance, power, influence, and visibility (Cillessen & Rose 2005, Parkhurst & Hopmeyer 1998. Adolescents' bids to enhance or maintain this form of peer status frequently involve the use of overt or relational aggression strategies that often are cited as powerful predictors of adolescent suicide (Juvonen & Graham 2014, Massing-Schaffer et al 2018. Adolescence also is marked by an increase in the frequency and emotional intimacy of dyadic peer experiences, with both best friendships and emerging romantic relationships occupying more of adolescents' attention and interest (Rose & Rudolph 2006, Steinberg & Morris 2001.…”
Section: The Adolescent Transitionmentioning
confidence: 99%
“…As compared with children and adults, adolescents report higher levels of peer-related interpersonal stressors and greater emotional reactivity to these types of stressors (Rudolph 2014). Note also that these peerrelated stressors (e.g., friendship alienation, romantic breakups, bullying) are among the most frequently reported precipitants to adolescents' suicidal behavior (Juvonen & Graham 2014, King & Merchant 2008, Massing-Schaffer et al 2018.…”
Section: The Adolescent Transitionmentioning
confidence: 99%
“…Although these studies do not directly compare ideators and attempters, by controlling for suicide ideation and using psychiatric samples, they provide information on the unique relation between stress and attempts. For example, three studies in clinical samples of adolescents found that, after adjusting for psychiatric symptoms and suicide ideation, major life events did not predict future suicide attempts (Daniel et al 2017; Massing-Schaffer et al 2019; Stone et al 2014). However, Stone and colleagues found an association between dependent life events and subsequent attempts among females, though this effect was not robust when controlling for participants’ suicide attempt history.…”
Section: Life Stress: Suicide Ideators Versus Suicide Attemptersmentioning
confidence: 99%